Training load structure of young soccer players in a typical training microcycle during the competitive and the transition period - Glowacki, A.; Ignatiuk, W.; Konieczna, A.; Jastrzebski, Z. (Baltic Journal of Health and Physical Activity, 2011)
Background: The aims of this study were: (1) to characterize the training load structure and the applied training means in typical microcycles of the transition period and the competitive season administered to young soccer players, and (2) to present exemplary training units of the competitive and the transition periods.